Aerogels: Amyloid Templated Gold Aerogels (Adv. Mater. 3/2016). Issue 3 (14th January 2016) - Nyström, Gustav; Fernández‐Ronco, María P.; Bolisetty, Sreenath; Mazzotti, Marco; Mezzenga, Raffaele
Abstract : A new class of ultralight gold materials is produced by combining amyloid fibrils with gold nanoparticles, as described by R. Mezzenga and co‐workers on page 472. The gold content of up to 20 karat equivalent allows the preservation of the optical properties of traditional gold alloys, yet at densities thousands of times lighter. By changing the colloidal gold shape, size, and concentration, the composition and material functionalities can be finely tuned, allowing catalysis and pressure‐sensing applications.